Biosensing: A General Strategy of Aerolysin Nanopore Detection for Oligonucleotides with the Secondary Structure (Small 18/2018). Issue 18 (3rd May 2018) - Liao, Dong‐Fang; Cao, Chan; Ying, Yi‐Lun; Long, Yi‐Tao
Abstract : Aerolysin‐based direct analysis of oligonucleotides with secondary structure (e.g., G‐quadruplex) remains a challenge. In article number1704520, Yi‐Lun Ying, Yi‐Tao Long, and co‐workers present a strategy employing an aerolysin nanopore to analyze structured oligonucleotides that are extended to 30 bases in length by a cation‐regulation mechanism. This method can in principle be applied to genetic and epigenetic biosensing, making it practical for diagnostics.